If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(10x + 24) = 0 Reorder the terms: x(24 + 10x) = 0 (24 * x + 10x * x) = 0 (24x + 10x2) = 0 Solving 24x + 10x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2x'. 2x(12 + 5x) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(12 + 5x)' equal to zero and attempt to solve: Simplifying 12 + 5x = 0 Solving 12 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 5x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 5x = 0 + -12 5x = 0 + -12 Combine like terms: 0 + -12 = -12 5x = -12 Divide each side by '5'. x = -2.4 Simplifying x = -2.4Solution
x = {0, -2.4}
| (s+16)(s+81)=0 | | 7-3x=15+5x | | 3-6(4+8n)=21+10n | | c(c+3)=0 | | y-(2y-5)=94 | | (3s+7)(s+6)=0 | | (3)-(-4)= | | s^2+11s+24=0 | | c^2-11c+18=0 | | 4x-7=3.5 | | -4(t+2)=12 | | s^7-7s=0 | | 32-14=3(x-4) | | -29+7x=-5(1-2x) | | 12x=6x+24 | | 12x=5x+24 | | 8y+2-6y=3+t-10 | | 5(3x-1)-3=25+4x | | z+2z= | | 12+3= | | -3x-8(1+x)=-2x+37 | | -9p(-6p+2)=-2p-9 | | 5(3z+7)=125 | | 1=12x^2+11x | | 15x^2-13x=0 | | 7x-6x=13+3x | | 5x^2-3x=8 | | 6x+8-2x(7-2)=2(6x+1) | | 4x^3-2x^2+12x=0 | | 2x^2=16x | | 36-6x=28 | | (x-9)(3x+1)=0 |